Transformasi Peran Terpuk Sitelu Dalam Pengelolaan Aset Strategis Desa Di Era Otonomi Daerah Di Desa Sukanalu Kecamatan Barusjahe - Ninta Br Sembiring, Emiya; Simson Ginting (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2026)
This study aims to analyze the transformation of the role of the Terpuk Sitelu customary institution in managing strategic village assets after the implementation of the village government system in the era of regional autonomy. The problem of this research stems from the lack of synchronization between the formal authority of the village government and the management practices of village assets, such as jambur and cemeteries, which are still dominated by the Terpuk Sitelu customary institution in Sukanalu Simbelang Village, Barusjahe District, Karo Regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. Data analysis was conducted using Ralph Linton's Role Theory to examine the dynamics of the status and social expectations of each actor. The results show that the role of Terpuk Sitelu has shifted from being the main decision-making institution to a cultural symbol that still has strong social legitimacy. The limitations of the village government in managing assets are caused by role conflicts, overlapping social expectations, and the absence of a formal collaboration mechanism between customary institutions and the village government. Abstrak Penelitian ini bertujuan untuk menganalisis transformasi peran lembaga adat Terpuk Sitelu dalam pengelolaan aset strategis desa setelah diberlakukannya sistem pemerintahan desa pada era otonomi daerah. Permasalahan penelitian ini berangkat dari adanya ketidaksinkronan antara kewenangan formal pemerintah desa dan praktik pengelolaan aset desa, seperti jambur dan pemakaman, yang masih didominasi oleh lembaga adat Terpuk Sitelu di Desa Sukanalu Simbelang, Kecamatan Barusjahe, Kabupaten Karo. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi lapangan, dan dokumentasi. Analisis data dilakukan menggunakan Teori Peran Ralph Linton untuk melihat dinamika status dan ekspektasi sosial masing-masing aktor. Hasil penelitian menunjukkan bahwa peran Terpuk Sitelu mengalami pergeseran dari lembaga pengambil keputusan utama menjadi simbol budaya yang tetap memiliki legitimasi sosial kuat. Keterbatasan pemerintah desa dalam mengelola aset disebabkan oleh konflik peran, tumpang tindih ekspektasi sosial, dan belum adanya mekanisme kolaborasi formal antara lembaga adat dan pemerintah desa.